Pseudo-elliptic narrow bandpass filter using shorted coupled-line of higher order design - Mohd Nasiruddin Hushim; Norfishah Ab Wahab; Muhammad Farid Abdul Khalid; Tn. Syarifah Atifah Tn. Mat Zin (Institute of Advanced Engineering and Science, 2019)
This paper presents an implementation of quarter wavelength single-shorted coupled-lines for narrow bandpass filter application. It is shown as a new way of creating a single resonance bandpass filter by inter-connected of two single-shorted quarter wavelength coupled-line sections. By adding more single-shorted coupled-line into the configuration, the form of halfwavelength resonator can increase the degree of order of the filter. For the design of 4th order resonator, the coupledlines are arranged inter-connected to each other forming five-fingers lines layout. Due to the interconnection of the coupledlines, transmission zeros appear at the two stopbands which improves the selectivity of the filter response. Investigation on the parametric of the 4th order resonator is conducted to observe the controlling parameters and it’s realiability responses of the resonator. For compactness, five-fingers meandered lines is proposed. It is found that the size of the meandered lines resonator was successfully reduced by 33% compared to the five-fingers straight lines resonator of the same order. For validation of concept, the 4th order meandered lines resonator was designed at 1 GHz and fabricated on RO3210 microstrip substrate with characteristics given as h = 1.27 mm, Ɛr = 10.2 and tan δ = 3x10-3. The measurement results show good agreement with the simulation results.